Penggunaan Alat Bantu Pembelajaran untuk Meningkatkan Hasil Belajar Passing Bolavoli pada Siswa X MAN 1 Kota Kediri Tahun Ajaran 2023/2024 - Fernanda, Mohammad Rullian Okta; Bekti, Ruruh Andayani; Muharram, Nur Ahmad (Jurnal Kridatama Sains dan Teknologi, 2024)
The aim of this research is to improve the learning outcomes of volleyball underpasses by applying assistive devices to Class This research is Classroom Action Research (PTK). This research was carried out in two cycles, consisting of four stages in each cycle consisting of planning, implementing actions, observing and reflecting. The research subjects were Class Data collection techniques using tests and observations. The results of data analysis in cycle I showed that 26 students (100%) succeeded in achieving the KKM in the knowledge aspect. In Cycle I of learning volleyball underpassing, social and spiritual attitude aspects, there was 1 student (4%) who received the Very Good (A) category, there were 23 students (88%) who received the Good (B) category, and there were 2 students ( 8%) received the Fair category (C). In Cycle I of learning volleyball underpassing, aspects of volleyball underpassing skills, there were 8 students (28%) who succeeded in reaching the KKM and 18 students (72%) who had not reached the KKM. In cycle II the learning outcomes increased again compared to cycle I in learning Under volleyball passing, there were 26 students (100%) who succeeded in reaching the KKM in the knowledge aspect. In Cycle II of learning volleyball underpassing, social and spiritual attitude aspects, there were 3 students (12%) who received the Very Good (A) category, there were 23 students (88%) who received the Good (B) category. In Cycle II of learning volleyball underpassing skills aspects of volleyball underpassing, there were 24 students (92%) who succeeded in reaching the KKM and 2 students (8%) who had not yet reached the KKM. Based on the results of this research, it is concluded that the application of assistive devices can improve the learning outcomes of volleyball underpassing in Class.